Các bạn ơi làm như này có đúng không ạ : -(2x-1)(x+3) = -(2x+1)(x+3) = -(2x^2+6x+x+3) = -(2x^2+7x+3)

Question

Các bạn ơi làm như này có đúng không ạ :
-(2x-1)(x+3)
= -(2x+1)(x+3)
= -(2x^2+6x+x+3)
= -(2x^2+7x+3)

in progress 0
Remi 5 tháng 2021-07-08T23:44:01+00:00 2 Answers 5 views 0

Answers ( )

    0
    2021-07-08T23:45:06+00:00

    Đáp án:

    sai ròi bn ơi `=-2x^2-5x+3` nhá

    Giải thích các bước giải:

     `-(2x-1)(x+3)`

    `=(1-2x)(x+3)`

    `=x+3-2x^2-6x`

    `=-2x^2-5x+3`

    0
    2021-07-08T23:45:50+00:00

    Đáp án:

     

    Giải thích các bước giải:

    -(2x-1)(x+3)

    = -(2x+1)(x+3)

    = -2x^2-6x+x+3

    = -2x^2-5x+3

     phá ngoặc ms đúng nhé bn!!

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )